2015
DOI: 10.1021/acs.energyfuels.5b01181
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for Obtaining High Quality Fuels from the Hydrocracking of a Hydrotreated Scrap Tires Pyrolysis Oil

Abstract: The hydrocracking of hydrotreated scrap tires pyrolysis oil (HT-STPO) has been studied aiming high-quality refinery blends for alternative automotive fuels. The hydrocracking runs have been carried out with a PtPd/SiO 2 -Al 2 O 3 catalyst in a fixed-bed reactor at 10 440-500 ºC, 65 bar and space time of 0.16 h. The catalyst has been characterized by ICP-AES, N 2 adsorption-desorption isotherms, and tert-butylamine adsorptiondesorption (TPD), while coke has been studied both quantitatively and qualitatively by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 62 publications
4
30
0
Order By: Relevance
“…The evolution of the product yields with time on stream is detailed in a previous work [20]. A similar effect with temperature was reported by Hita et al [35] for the same process using a Pt-Pd/SiO 2 -Al 2 O 3 catalyst in the 440-500°C range. In that case, a decrease of 40 % of the initial activity was observed at 440°C.…”
Section: Catalyst Deactivationsupporting
confidence: 74%
See 1 more Smart Citation
“…The evolution of the product yields with time on stream is detailed in a previous work [20]. A similar effect with temperature was reported by Hita et al [35] for the same process using a Pt-Pd/SiO 2 -Al 2 O 3 catalyst in the 440-500°C range. In that case, a decrease of 40 % of the initial activity was observed at 440°C.…”
Section: Catalyst Deactivationsupporting
confidence: 74%
“…The existence of phosphate groups on the fresh catalyst surface resulting from the chemical activation with H 3 PO 4 is proven by the P:O ratio measured through XPS [36]. This P-containing groups, with acidic character, provide the catalyst with a total acidity comparable to that of a silica-alumina support [35]. Regarding deactivated catalysts, a remarkable drop of surface area (ca.…”
Section: Catalyst Deactivationmentioning
confidence: 95%
“…One of the main drawbacks of this reaction is the catalyst deactivation due to the formation of carbonaceous deposits (coke), which also causes operational difficulties [23][24][25][26][27][28]. This formation of coke is related to the thermal instability and repolymerization of the phenolic components of bio-oil.…”
Section: Introductionmentioning
confidence: 99%
“…Lovás et al [20] compared the catalytic cracking in FCC conditions of high-density polyethylene (HDPE) and polypropylene (PP) waxes together with VGO and it was concluded that PP should be used preferentially in order to boost gasoline production. On the other hand, the condensed pyrolysis oil derived from waste (scrap) tires also shows great prospects to become a FCC feed and produce high quality fuels [21][22][23]. Concerning oxygenated bio-derived streams (iii), a great research interest has been directed towards exploring the possibilities of bio-derived feedstock (i.e., bio-oil and vegetable oils) for FCC conversion [24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%